Analisis Kinerja Pegawai pada Dinas Perpustakaan Kabupaten Aceh Tenggara - Rusaidi Rusaidi; Maksum Syahri Lubis; Humaizi Humaizi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Employee performance is a very important thing in the organization's efforts to achieve its goals, to improve employee performance, it means that it requires the ability of employees to carry out work. Constraints that often occur are employees who do not have the ability, lack of discipline and do not serve well. The formulation of the research problem is how the performance of the Southeast Aceh Regency library service employees and what factors are the obstacles to the performance of Southeast Aceh Regency Library Service employees. The results of the research that the performance of library service employees do not have good quality. Constraints faced are limited facilities and infrastructure, employee competence is still very low, librarian education and training for employees has never been carried out and the availability of budget allocations is very limited. It is recommended that the Southeast Aceh District Library Service conduct professional training for librarians to be given to every library employee. The regional government of Aceh Tenggara Regency should allocate a budget according to need, in order to improve library services, because the budget allocation will accelerate the improvement of employee performance in services.